Efektivitas Pembelajaran Tema Selalu Berhemat Energi Bermuatan Sustainability Menggunakan Model Problem Based Learning Terhadap Pemahaman Konsep - Arlindra Rizma Saputri; Siti Patonah; Mudzanatun (JANACITTA, 2023)
The aim of the study was to test the effectiveness of the problem-based learning model with sustainability on the conceptual understanding of fourth grade students at SD Negeri 01 Protomulyo. The research carried out was of a quantitative type using an experimental method in the form of a One-Group Pretest – Posttest Design used in one group. The results obtained from the research show that student learning outcomes have increased compared to the results of the pretest and posttest, so that it can be concluded that the problem based learning model contains sustainability is effective on science learning outcomes for fourth grade students at SD N 01 Protomulyo. Based on the results of this study, suggestions can be given so that teachers can implement problem-based learning models with sustainability in order to create effective and enjoyable learning for students.   Tujuan penelitian ialah untuk menguji keefektifan model problem based learning bermuatan sustainability terhadap pemahaman konsep siswa kelas IV SD Negeri 01 Protomulyo. Penelitian yang dilaksanakan berjenis kuantitatif dengan menggunakan metode eksperimen berbentuk One-Group Pretest–Posttest Design yang digunakan pada satu kelompok. Hasil yang didapat dari penelitian menampilkan bahwasanya hasil belajar siswa meningkat dibandingkan hasil pretest dan posttest, sehingga dapat diambil simpulan bahwasanya model Problem Based Learning bermuatan sustainability efektif terhadap hasil belajar IPA siswa kelas IV SD N 01 Protomulyo. Berdasar hasil penelitian ini, dapat diberikan saran agar guru bisa mengimplementasikan model Problem Based Learning bermuatan sustainability agar tercipta pembelajaran efektif serta menyenangkan untuk siswa.